Dual‐loop SFC scheme for BTB‐VSC‐HVDC interconnecting asynchronous AC grids. Issue 16 (18th January 2019) - Zeng, Lingkang; Li, Dahu; Yao, Wei; Sun, Jianbo; Wen, Jinyu
Abstract : This study proposes a dual‐loop supplementary frequency control (SFC) scheme for back‐to‐back voltage source converter high‐voltage DC (BTB‐VSC‐HVDC) interconnecting asynchronous AC grids, to provide frequency support for each other after a large disturbance. The proposed dual‐loop SFC consists of the frequency‐active power ( f–P ) loop and the frequency‐reactive power ( f–Q ) loop. The former deployed on the P ‐loop of VSC‐HVDC can provide frequency support for the disturbed grid during the primary frequency regulation and improve the steady‐state characteristics of the frequency response, while the latter attached to the Q ‐loop of VSC‐HVDC supports virtual inertia to ameliorate the transient characteristics of the frequency response. Simulation studies are conducted based on the equivalently simplified model of Southwest Power Grid and Hubei Power Grid interconnected by Chongqing‐Hubei BTB‐VSC‐HVDC. Simulation results show that the proposed SFC scheme can effectively improve the transient and steady‐state characteristics of the system frequency response under a wide range of operating condition.